Tips on Learning from Context: Formal and Informal Approaches to Understanding the Local Political Economy - and Swift, Sarah (USAID, 2018)
Successfully adapting your programmatic efforts and policy engagement to the context depends on maintaining your understanding of that context. Given this, continuous learning and feedback loops–not only about your programming, but also about the environment you are working within–are important components of USAID’s work. Since our environments are always changing, in ways big and small, this can be intimidating. One can imagine a scenario where learning consumes the limited time and budgets available, especially for small programs. The question becomes: How can we learn enough, at the right times, to limit missed opportunities and warning signs, while avoiding being consumed by data collection and analysis that never influences our work? This document capitalizes on the experiences of USAID staff as well as emerging learning from other donors and researchers to highlight a range of approaches–formal and informal, time-bound and continuous–that can support ongoing learning within the operational tempo of a busy Mission team or Operating Unit.